Variability By Region and Season of Polycyclic Aromatic Hydrocarbons in Oil Field Soil in Southern Iraq's Basrah Governorate: Variabilitas Berdasarkan Wilayah dan Musim Hidrokarbon Aromatik Polisiklik di Tanah Ladang Minyak di Kegubernuran Basrah, Irak Selatan - Resen, Majdalena’’ A.; Abdulhassan, Hamza K.; AL-Saad, Hamid T. (Indonesian Journal on Health Science and Medicine, 2024)
Soil samples were gathered from 11’ oil fields in the Basrah governorate, including (Seba, Safwan, Majnoon, Ratawi, Bergezia, West Qurna 1, West Qurna 2, Shuaaba, South and North Rumaila, and Zubair), at a depth of 0 to 20 cm. The aim was to determine the distribution and origin polycyclic aromatic hydrocarbons (PAHs), they were divided into two major groups according to their molecular weight. The first group included six low molecular weight (LMW) chemicals: naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, and anthracene, each containing two to three fused aromatic rings. The second group consisted of nine high molecular weight (HMW) compounds with four or more fused aromatic rings: Fluoranthene, Pyrene, Benzo(a)anthracene, Chrysene, Benzo’’(b)fluoranthene, Benzo(k)fluoranthene, Benzo(a)Pyrene, Indeno (1,2,3, c,d) Pyrene, and Benzo(g,h,i)perylene. Station 8 (Shuaaba) recorded the highest mean concentration of total PAHs at 2374.85 ng/g dry weight, while Station 3 (Majnoon) recorded the lowest at (370.672ng/g) dry weight. The PAHs origin was attributed to both pyrogenic and petrogenic sources, as determined by the ratios of LMW/HMW, Phenanthrene/Anthracene, and Fluoranthene/Pyrene. The PAHs compound came from pyrogenic and petrogenic organisms, as indicated by the ratios of LMW/HMW, Phenanthrene/Anthracene, and Fluoranthene/Pyrene. Seasonal mean concentrations of PAHs were in winter (1375.541 ng/g) and summer (529.496 ng/g), with autumn having the lowest concentration (304.486 ng/g), arranged in this order: (Winter > Spring > Summer > Autumn). Highlights: PAHs in Basrah Soil: Highest in Shuaaba (2374.85 ng/g), lowest in Majnoon (370.67 ng/g). Source & Classification: PAHs from pyrogenic and petrogenic origins, classified by LMW/HMW ratios. Seasonal Variation: Highest in winter (1375.54 ng/g), lowest in autumn (304.49 ng/g). Keywords: PAHs,GClMS. Soil pollution, Oil fields, Basrah